Construção identitária no mundo digital: uma análise da influência do marketing nas redes sociais no público infantojuvenil - Rolim, Rebeca Barreiros (2024)
Social media plays an increasingly crucial role in the lives of children, providing early access to a vast digital world filled with learning opportunities. However, this online interaction also exposes boys and girls to a variety of advertisements on social networks. This study aimed to investigate how influencer marketing on social media affects the identity construction of children and adolescents. To this end, themes such as identity formation, social identity theory, the impact of digital influencers and social media marketing, and the role of technology in the identity development of children and adolescents were explored. The research highlighted the importance of understanding how interaction with the digital environment shapes children's perceptions and influences their behavior. Additionally, it emphasized the need to promote conscious consumption and ethical practices in the digital environment, aiming for the well-being and healthy development of this new generation. The study adopted a qualitative approach, using focus groups with children aged 8 to 11 years to investigate their mobile phone and social media usage habits, parental supervision in this context, and feelings related to consumption and identity. The content analysis of the data, conducted with the help of Maxqda software, sought to elucidate the children's perceptions and experiences in this scenario, examining whether digital exposure can generate negative feelings and influence children's identity either positively or negatively. The method included playful activities to facilitate interaction and the collection of pertinent information. The results highlighted that children are exposed to content and influencers on social media, which can shape their values, perceptions, and identity aspirations. The lack of parental supervision and children's discernment in the use of digital platforms intensifies their vulnerability to the messages conveyed by influencers, underscoring the need for guidance from responsible adults